Durkheim's Mechanical Solidarity in Practice: Insights from the Honda Astrea Rider Community in Singkawang - Fazrul, Muhammad; Bahari, Yohanes; Utami, Patrisia Rahayu; Sikwan, Agus; Wahyuni, Fauziah Sri (Universitas Tanjungpura, 2025)
This study aims to analyze the form of mechanical solidarity within the Honda Astrea Rider Club (HARC) community in Singkawang through the perspective of Émile Durkheim. The research employed a descriptive qualitative method with four informants selected using purposive sampling, supported by interviews, observations, and documentation. The findings indicate that mechanical solidarity in HARC is manifested through three main aspects: first, collective consciousness in the form of shared values of togetherness, kinship, and mutual assistance, which shape the group’s identity; second, normative consensus reflected in members’ adherence to community rules, maintained by the role of the leader and reinforced by social sanctions; and third, a simple division of labor without role specialization, where all members participate equally based on the principle of mutual cooperation. These findings affirm that mechanical solidarity continues to exist in modern communities built on shared interests and common values, while also contributing to sociological studies on the relevance of Durkheim’s theory in contemporary contexts and opening opportunities for further research on the potential shift from mechanical to organic solidarity within motorcycle communities.